Teaching writing to children in indigenous languages
1 online resource (1 volume)
Keywords: This volume brings together studies of instructional writing practices and the products of those practices from diverse Indigenous languages and cultures. By analyzing a rich diversity of contexts--Finland, Ghana, Hawaii, Mexico, Papua New Guinea, and more--through biliteracy, complexity, and genre theories, this book explores and demonstrates critical components of writing pedagogy and development. Because the volume focuses on Indigenous languages, it questions center-margin perspectives on schooling and national language ideologies, which often limit the number of Indigenous languages taught, the domains of study, and the age groups included.